Odpowiedzi

2009-11-20T14:54:57+01:00
Udowodnij prawo przechodno sci implikacji
[(p=>q)^(q=>r)]=>(p=>r)

IrIpIqIp=>qIq=>rI(p=>q)^(q=>r)Ip=>rI[(p=>q)^(q=>r)]=>(p=>r)I
1 1 1 1------1---------1------------1---------------------1
1 1 0 0------1---------0------------1---------------------1
1 0 1 1------0---------0------------1---------------------1
1 0 0 1------1---------1------------1---------------------1
0 1 1 1------1---------1------------0---------------------1
0 1 0 0------1---------0------------0---------------------1
0 0 1 1------0---------0------------1---------------------1
0 0 0 1------1---------1------------1---------------------1
1 5 1